Aproaches to Forming the Company’s Strategic Goals - QINGSEN, LI; ARTEMENKO, L. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2022)
Defining the general direction of the organization, namely the vision, mission and its corporate values, is the primary goal of forming strategic goals. Vision of the future of the company is becoming an increasingly important element. Management can develop several alternative strategic scenarios and evaluate them in terms of the organization’s long-term goals. To begin implementing the chosen strategy (or to continue re-validation), management specifies it in terms of actions to be taken in the near future. The article considers the concept of “strategy”, the process of developing a strategy for the company, the importance of the mission and goals for the development of the company, as well as the requirements, compliance with which allows one to develop an optimal strategy for the organization. The model of a choice of the company’s strategic orientation is propose. The steps that allow companies to develop a strategic process are identified.